Effect of Heat Treatment on Microstructure and Mechanical Properties of Mg-5Zn-1Mn Alloy Tube - Lianhui Li; Hongshuai Cao; Fugang Qi; Qing Wang; Nie Zhao; Yingdu Liu; Xue Ye; Xiaoping Ouyang (Metals, 2020)
The effects of heat treatment on the microstructure, mechanical properties and electrochemical property of the as-extruded Mg-5Zn-1Mn (ZM51) alloy tube are investigated by optical microstructure (OM), X-ray diffractometer (XRD), scanning electron microscopy (SEM), transmission electrical microscope (TEM), uniaxial tensile test, and electrochemical test. The results show that the as-cast structure is a typical dendritic structure, mainly composed of α-Mg and Mg7Zn3 eutectic compounds. After homogenization, most of Mg7Zn3 eutectic phases are dissolved in the Mg matrix. During the extrusion process, the ZM51 alloy has undergone complete dynamic recrystallization and has a good elongation, reaching 21.4%. T6, especially T4 + double aging treatment, can significantly improve the mechanical properties of the as-extruded tube. The microstructure reveals that the precipitation strengthening of the finely dispersed MgZn2 precipitates is the main reason for the strength increase. The fracture micromorphology of the as-extruded tube is mainly composed of dimples and cleavage facets, which is a typical ductile fracture. The fracture mode of the as-aged alloy tubes belongs to cleavage fracture. In addition, the electrochemical test results show the solution-treated ZM51 alloy tube has the best corrosion resistance. The improvement of corrosion resistance is mainly due to the microstructure uniformity and low phase volume fraction.